Etching and coating mechanisms evaluation of gold nanoparticles-coated surface plasmon resonance sensors in protic solvents - Elshikeri, Nada Badreldin Ibrhim (2022)
In recent years, the demand for high-quality sensors for various industrial, medical and environmental applications has been exponentially growing. Based on these facts, four gold nanoparticles (AuNPs)-coated surface plasmon resonance sensors were fabricated through etching and coating processes in the protic solvents. The performance of the designed localized surface plasmon resonance (LSPR)-based sensors were optimized in terms of their repeatability, selectivity, sensitivity, and linearity parameters. The Weibull etching and coating mechanisms in the protic solvents were evaluated using the fabricated sensors. The AuNPs size and optical fibre diameter dependent organic solvents parameters (SP) enable to achieve a high-performance sensing useful for varied applications. The etching and coating mechanisms were shown to play a significant role in the obtained sensors performance. These sensors' sensitivity, selectivity, repeatability, and linearity were determined using varied laser-ablated energies (LAE) of 240, 250, 260, and 270 mJ. Protic solvents such as ethanol, methanol, 1-propanol, and 1-butanol were used for the measurements. Three mechanisms for etching and coating were proposed wherein the first one before the solvent inclusion, second one after dipping the LSPR-sensor in the protic solvent, and the last one after withdrawing the solvent from the LSPR-sensor. A comparative evaluation of the sensing performance was made using the Weibull analysis and survival analysis test. The Weibull analysis demonstrated the best outcomes for the diameter and thickness measurements, indicating that more than one measurement can produce better comparability of sensitivity (up to 72 for 260 mJ LAE-sensor) and selectivity (in methanol). Among all four solvents, methanol revealed the most significant influence on the sensing performance, ascribed to the formation of Au-OH and Au-CH bonds surrounding the plasmonic AuNPs. Besides, the solvent's highest polarity factors, dielectric constant, hydrogen-bond donor, lowest refractive index, and molarity played a vital role. The Weibull method was shown to be most suitable for analysing the sensor's sensitivity, performance and certainty, thus paving the way for designing susceptible devices.